The Effectiveness of Improving Vocabulary Mastery in Reading by Using Extensive Reading for Junior High School Number 6 Jambi - Amirah, Amirah; Wennyta, Wennyta (Universitas Batanghari Jambi, 2024)
The researcher was interested in conducting the research entitled “Improving Students Vocabulary Mastery in Reading by Using Extensive Reading for Junior High School Number 6 Jambi City. Based on the identification of the problem above, the researcher wants to figure out the effect of extensive reading on students'' vocabulary mastery. Then the researcher used quantitative research (Experimental). This study was only conducted in one class. Pretests and post-tests were given to students. The results showed that the students'' vocabulary improved significantly after the treatment using an extensive reading approach. It was revealed by the post-test mean score of 82.89, which was higher than the pre-test score of 66.71. Based on the results of the data above using IBM SPSS Statistics 25, the two-tailed significant or sig. (2-tailed) was 0.00 at the level of Sig α 0.05. Based on these results Ha (alternative hypothesis) is accepted and H0 (Null hypothesis) is rejected. Therefore, it can be concluded that there is a significant difference between the scores obtained by the students in the pre-test and post-test. The researcher concluded that the use of the Extensive Reading approach was effective in increasing the students'' vocabularies.